Assessing community participation in health promotion programs: a case study of maldives / Asma Ibrahim Sulaiman - Ibrahim Sulaiman, Asma (2015)
This study assessed the participation of Maldives community in health promotion programme, namely, decision making, implementation, benefit sharing and evaluation. This study, which was conducted in the Maldives, also examined the factors associated with participation in health promotion programme. Adopting the survey method, the pre-tested interview schedule was administered to the random sample of 1,070 respondents from 3 selected atolls. The survey adopted a self-report technique. Multi-stage cluster sampling techniques were used to select the respondent for this study. The total geographical area was divided into 7 provinces and 3 provinces from Upper North, North Central and Upper South were taken for this study. The response rate of the survey was 86% (n=923). Data gathered from the survey was supported with secondary data gained from the office records and library research. All data were analyzed using the Statistical Package for the Social Sciences (SPSS). The Maldives community who involved in this study was heterogeneous in terms of their socio-demographic attributes and participated in health promotion programme through political party. By and large, the level of participation measured along four clusters of factors, was occasionally and uncertain. High level of participation prevailed only among a small proportion of Maldives community. The notion of ‘uncertain’ may itself is ultimate barriers to participation. In this appeal the participation of rural community groups may be significantly difference from participation of mainstream community members in terms of motivation, constraints and strategies which are necessary to make it meaningful and effective. The chi-square analysis shows that structural, operational and community factors are significantly association with the level of community participation. In relation to the interest of study findings the government needs to reconsider in modifying the current ii practice, and a number of practical recommendations for strengthening community participation in health promotion can be explored by implementation of the proposed “Community –based intervention on health promotion module”.